A green recycling process of the spent lead paste from discarded lead–acid battery by a hydrometallurgical process. Issue 5 (May 2019) - Zhu, Xinfeng; Zhang, Wei; Zhang, Liying; Zuo, Qiting; Yang, Jiakuan; Han, Lu
In this study, a green recycling process of discarded lead–acid battery paste, which could avoid both the smelting and electro-winning route has been developed. Leaching reagents containing sodium citrate, acetic acid and hydrogen peroxide were reacted with spent lead paste in aqueous media at the pH of 5–6. Lead paste was leached and formed into lead citrate precursor, which was recrystallized and separated from the solution. The optimal conditions for the leaching process at room temperature were found to be the: concentration of acetic acid solution of 0.92 mol L -1 ; concentration of sodium citrate solution of 0.478 mol L -1 ; initial mass ratio of solid spent lead paste to liquid (solid/liquid ratio) of 1/5 g/mL; and reaction time of 2 hours. The results showed that the desulphurization efficiency of lead paste was up to 99.9%. The optimal conditions for lead citrate re-crystallization from the leaching mixed solution were found to be the re-crystallization temperature of 55 o C for 5 hours in a water bath. The lead citrate precursor synthesized from discarded lead–acid battery pastes was the chemical formula of Pb3 (C6 H5 O7 )2 ·3H2 O with columnar shape in the length of 30–50 μ m, which was easily separated from the leaching solution. The results of kilogram-scale experiments made progress easier for obtaining the ultrafine lead oxide product (PbO and Pb) from discarded lead–acid battery paste.